Therapeutic gas‐releasing nanomedicines with controlled release: Advances and perspectives. Issue 5 (25th May 2022) - Opoku‐Damoah, Yaw; Zhang, Run; Ta, Hang T.; Xu, Zhi Ping
Abstract: Nanoparticle‐based drug delivery has become one of the most popular approaches for maximising drug therapeutic potentials. With the notable improvements, a greater challenge hinges on the formulation of gasotransmitters with unique challenges that are not met in liquid and solid active ingredients. Gas molecules upon release from formulations for therapeutic purposes have not really been discussed extensively. Herein, we take a critical look at four key gasotransmitters, that is, carbon monoxide (CO), nitric oxide (NO), hydrogen sulphide (H2 S) and sulphur dioxide (SO2 ), their possible modification into prodrugs known as gas‐releasing molecules (GRMs), and their release from GRMs. Different nanosystems and their mediatory roles for efficient shuttling, targeting and release of these therapeutic gases are also reviewed extensively. This review thoroughly looks at the diverse ways in which these GRM prodrugs in delivery nanosystems are designed to respond to intrinsic and extrinsic stimuli for sustained release. In this review, we seek to provide a succinct summary for the development of therapeutic gases into potent prodrugs that can be adapted in nanomedicine for potential clinical use. Abstract : This review takes a critical look at four key gasotransmitters (CO, NO, H2 S and SO2 ) with their incorporation into prodrugs known as gas‐releasing molecule. Different nanosystems and their mediatory roles for efficient shuttling, targeting and cleavage of therapeutic gases and the responsiveness to typical internal and external stimuli for gas release from prodrugs have been reviewed extensively.